Efek protektif sari kurma (Phoenix dactylifera L.) terhadap histopatologi paru mencit yang terpapar asap rokok - Christianty, Fransiska; Arizka, Hawwin Elina; Holidah, Diana (Journal of Agropharmacy, 2024)
Smoking has become a lifestyle that affects human health and causes many diseases, including respiratory system disorders, cancer, infertility, and cardiovascular diseases. Cigarette smoke contains harmful ingredients that trigger the formation of free radicals that can damage cells. Dates become a source of antioxidants. Some studies showed that dates have high antioxidant activity due to their compounds, such as carotene, flavonoids, and phenolic acids. Date palm fruit juice is widely sold on the market, but date research on fruit juice is still limited. The present study was designed to evaluate the preventive effect of date palm fruit juice in lung histopathology of mice induced by cigarette smoke. Twenty-four mice were exposed to cigarette smoke and then treated with date palm juice in different doses (5, 10, and 20 ml/kg BW) daily for 14 days. On the 15th day, mice were sacrificed, and the lung organ was separated for microscopic observation. The results showed that starting a low dose of date fruit juice treatment can minimize lung damage comparable to vitamin C, based on the histopathological profile and scoring of the lung damage. These findings suggest that date juice has been proven to have a protective effect in preventing and reducing lung damage due to exposure to cigarette smoke through its antioxidant activity.